Implementasi Pembelajaran IPA Berbasis Digital di Sekolah Dasar: Studi pada SD Negeri 17 Cegek - Felia Hafifah; Elfia Sukma; Inggria Kharisma (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the implementation of digital-based science learning at SD Negeri 17 Cegek, determine student responses to the use of digital media, and identify various obstacles faced and solutions in its implementation. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. This study was conducted at SD Negeri 17 Cegek. Using a total sampling technique, all 12 fifth-grade students were made research subjects. The selection of subjects was based on the consideration that the class was a class that was directly observed. The results of the study showed that the application of digital media was able to increase learning motivation, attention, and active participation of students in science learning. Students became more interested and more easily understood the material presented because the learning presentation was more interactive and rich in visual elements. However, the implementation of digital-based learning still faces several obstacles, including limited facilities and infrastructure, unstable internet access, and teachers' lack of technological competence. Therefore, better support is needed, including adequate facilities and teacher competency development, to ensure optimal implementation of digital-based learning in elementary schools. At Cegek 17 Public Elementary School, science learning is still dominated by lectures and textbooks. The use of digital media has not been maximized. Teachers are expected to continue improving their competency and skills in using technology and digital learning media. The school is expected to provide concrete support by providing facilities and supporting tools for digital learning